2018
DOI: 10.1186/s13256-018-1843-4
|View full text |Cite
|
Sign up to set email alerts
|

Superior vena cava syndrome in a patient with locally advanced lung cancer with good response to definitive chemoradiation: a case report

Abstract: BackgroundThe incidence of superior vena cava syndrome within the United States is roughly 15,000 cases per year. Superior vena cava syndrome is a potentially life-threatening medical condition; however, superior vena cava syndrome is not fatal in the majority of cases. Superior vena cava syndrome encompasses a collection of signs and symptoms resulting from obstruction of the superior vena cava, including swelling of the upper body of the head, neck, arms, and/or breast. It is also associated with cyanosis, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 11 publications
(12 reference statements)
1
15
0
3
Order By: Relevance
“…Superior vena cava syndrome requires high index of suspicion for early diagnosis and prompt therapy. The common symptoms include dyspnea, cough, cyanosis, facial plethora, distension of neck and chest wall veins and occasionally arm swelling [9]. These symptoms were seen in our case, as well.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Superior vena cava syndrome requires high index of suspicion for early diagnosis and prompt therapy. The common symptoms include dyspnea, cough, cyanosis, facial plethora, distension of neck and chest wall veins and occasionally arm swelling [9]. These symptoms were seen in our case, as well.…”
Section: Discussionsupporting
confidence: 76%
“…Chemotherapy-sensitive malignancy respond rapidly (within weeks) to chemotherapy. However, for more chemo-resistant tumors, a combination of chemotherapy, radiotherapy and/or endovascular stenting may be considered [9]. In our case, the patient had a chemo-sensitive disease and responded well to chemotherapy and steroids and did not require any endovascular intervention.…”
Section: Discussionmentioning
confidence: 82%
“…3 Signs and symptoms include swelling of the face, head, neck, breast, cough, dyspnea, distended neck veins, orthopnea, and conjunctival suffusion; collateral circulation leads to distension of superficial veins in the chest wall. 3 Other less common symptoms of SVC syndrome include stridor, hoarseness, dysphagia, pleural effusion, head plethora, headache, nausea, lightheadedness, syncope, change in vision, altered mental status, upper body edema, cyanosis, papilledema, stupor, and coma. 1 Some rare but serious clinical consequences reported in SVC syndrome include cerebral edema and upper respiratory compromise secondary to edema of larynx and pharynx.…”
Section: Resident Discussionmentioning
confidence: 99%
“…In the past, it was thought that tumor compression was the main cause of superior vena cava syndrome caused by tumors. Hinton et al reported a case of a non-small cell lung cancer patient, who received chemotherapy, and the tumor was reduced by more than 50%, but the superior vena cava stenosis was not relieved [ 7 ]. Lanciego recommends Wallstent endoprosthesis as the first choice for palliative treatment of superior vena cava syndrome [ 8 ].…”
Section: Introductionmentioning
confidence: 99%